Reduced-order modeling of lattice structures through iterative beam fitting and static mesoscale projection - Nicolas Grünfelder; Manmit Padhy; Alaa Armiti-Juber; Seyed Morteza Seyedpour; Navina Waschinsky; Tim Ricken (Results in Engineering)
Lattice structures exhibit a wide range of advantageous properties, making them highly compelling to both industrial applications and academic research. However, they also present significant challenges, foremost being the substantial computational cost in numerical simulations. While high-fidelity simulations may suffice for small-scale examples typically found in the literature, they become impractical for real-world components with large numbers of unit cells and repeated execution of the simulations. To address this issue, a model order reduction method (MOR) is proposed in this study, transitioning from a high-fidelity solid model to a computationally more efficient lower-fidelity beam model. This reduction in model complexity is accompanied by a local fitting process of the individual unit cells, also referred to as the mesoscale, that mitigates the errors typically introduced by the simplified beam representation. Additionally, the high-fidelity mesoscale is represented efficiently through the static condensation technique for repeating unit cells with varying boundary conditions. The developed approach enables the creation of a resulting substitute model that maintains high accuracy while offering substantial computational savings. This enables the efficient analysis and optimization of auxetic and non-auxetic lattice structures at scales relevant to practical engineering applications.